Synthesis of Some Biologically Active 3-Methyl-4- (substituted phenylhydrazono)-2-pyrazolin-5-ones and 2-Isoxazolin-5-ones - RAJPUT, A.P.; RAJPUT, S.S. (Asian Journal of Chemistry, 2010)
Diazotized substituted anilines were treated with ethyl aceto acetate to yield ethyl-2-(substituted phenyl) hydrazono-3-oxo butyrates (I). Reaction of I with various ammonia derivatives (PhNHNH2, H2NNH2, H2NOH·HCl) furnished pyrazoline-5-ones, isoxazoline-5 ones. The synthesized compounds have been tested for their biological activity.